2015
DOI: 10.1111/bph.13132
|View full text |Cite
|
Sign up to set email alerts
|

Atenolol offers better protection than clonidine against cardiac injury in kainic acid‐induced status epilepticus

Abstract: BACKGROUND AND PURPOSEStatus epilepticus is increasingly associated with cardiac injury in both clinical and animal studies. The current study examined ECG activity for up to 48 h following kainic acid (KA) seizure induction and compared the potential of atenolol and clonidine to attenuate this cardiac pathology. EXPERIMENTAL APPROACHSprague-Dawley rats (male, 300-350 g) were implanted with ECG and electrocorticogram electrodes to allow simultaneous telemetric recordings of cardiac and cortical responses durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
25
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(30 citation statements)
references
References 72 publications
5
25
0
Order By: Relevance
“…Previous work by our group demonstrated that SE resulted in an immediate elevation in sympathetic activity, leading to structural cardiac damage and seizure‐induced cardiomyopathy . Our group also confirmed that pretreatment with sympatholytics could protect the heart during seizure . This current study broadens our understanding by investigating whether intervening in seizure progression with diazepam has any beneficial impact on the associated development of cardiomyopathy in seizure.…”
Section: Introductionsupporting
confidence: 81%
See 1 more Smart Citation
“…Previous work by our group demonstrated that SE resulted in an immediate elevation in sympathetic activity, leading to structural cardiac damage and seizure‐induced cardiomyopathy . Our group also confirmed that pretreatment with sympatholytics could protect the heart during seizure . This current study broadens our understanding by investigating whether intervening in seizure progression with diazepam has any beneficial impact on the associated development of cardiomyopathy in seizure.…”
Section: Introductionsupporting
confidence: 81%
“…Clinical studies have shown that atenolol is effective at attenuating ischemic damage and improving left ventricular function . Prophylactic atenolol administration has been shown to prevent tachycardia and protect against seizure‐induced QTc prolongation in rat models of SE …”
Section: Introductionmentioning
confidence: 99%
“…8,11 Furthermore, pharmacologic blockade of the β-adrenergic receptors prior to seizure induction have prevented QTc prolongation and T-wave abnormalities, decreased arrhythmogenic potential and myocardial damage, and preserved left ventricular function in SE animals. 32,33 Together, these findings suggest that cardiac sympathetic activation may play a significant role in SE-associated pathologic changes of the myocardium. Indeed, in our study, the SE animals exhibited decreased β1-AR protein levels, a finding that is consistent with adrenergic receptor desensitization due to persistent sympathetic stimulation and a common pathologic alteration in heart failure.…”
Section: Discussionmentioning
confidence: 88%
“…Finally, RDN has been demonstrated to attenuate sympathetic outflow via the central nervous system to the heart and other organs 9. It has been reported that noninvasive methods of central sympathetic inhibition, such as clonidine, might have a cardioprotective effect 39. Therefore, this noninvasive method may yield results similar to RDN.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, this noninvasive method may yield results similar to RDN. However, it has been considered that high doses of clonidine are required to regulate sympathetic activity and adverse effects (eg, sedation and dry mouth) will be commonly caused 39, 40. Therefore, the effect of RDN might be still better than that in drugs in terms of sympathetic inhibition.…”
Section: Discussionmentioning
confidence: 99%